2024
DOI: 10.3389/fmicb.2023.1336537
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation unveils sex-specific differences in a controlled cortical impact injury mouse model

Tulasi Pasam,
Manoj P. Dandekar

Abstract: IntroductionContusion type of traumatic brain injury (TBI) is a major cause of locomotor disability and mortality worldwide. While post-TBI deleterious consequences are influenced by gender and gut dysbiosis, the sex-specific importance of commensal gut microbiota is underexplored after TBI. In this study, we investigated the impact of controlled cortical impact (CCI) injury on gut microbiota signature in a sex-specific manner in mice.MethodsWe depleted the gut microflora of male and female C57BL/6 mice using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Female mice have higher ROS activities in the brain in the acute phase [ 70 ]. Glial cells in female mice are also less activated in the subacute phase of brain injury [ 71 ].Meanwhile, recent studies also found that post-CCI neurological complications may be influenced by the differential gut microbiota perturbation in a gender-dependent manner [ 72 ]. Thus, in order to minimize the confounding factors caused by gender, only single-sex mice were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Female mice have higher ROS activities in the brain in the acute phase [ 70 ]. Glial cells in female mice are also less activated in the subacute phase of brain injury [ 71 ].Meanwhile, recent studies also found that post-CCI neurological complications may be influenced by the differential gut microbiota perturbation in a gender-dependent manner [ 72 ]. Thus, in order to minimize the confounding factors caused by gender, only single-sex mice were used in this study.…”
Section: Discussionmentioning
confidence: 99%